Sikap Keluarga dalam Pencegahan Stunting - Hunggumila, Antonetha; Noviana, Ineke; Ridja, Tatu (JURNAL KESEHATAN PRIMER, 2021)
Background: Stunting has not been resolved to date and is still a major problem. The government's efforts to prevent stunting have been implemented through nutrition programs with sensitive interventions and specific interventions have not shown maximum results.  The aim of this research is to determine family attitudes in preventing stunting. Method: This type of research is a descriptive method. The population was 122 families, while the sample used was 30 families in Mbatakapidu Village in 2021. The sampling technique used was a purposive sampling technique, namely a questionnaire. The data was analyzed univariately.  Results: Based on the research results, 21 respondents (70%) had good attitudes and 9 respondents (30%) had poor attitudes.  Conclusion: 21 respondents (70%) had a good attitude and 9 people (30%) had a poor attitude.